2018
DOI: 10.1186/s40246-018-0150-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of gene expression and associated mutation profiles of APOBEC3A, APOBEC3B, REV1, UNG, and FHIT with chemosensitivity of cancer cell lines to drug treatment

Abstract: BackgroundThe APOBEC gene family of cytidine deaminases plays important roles in DNA repair and mRNA editing. In many cancers, APOBEC3B increases the mutation load, generating clusters of closely spaced, single-strand-specific DNA substitutions with a characteristic hypermutation signature. Some studies also suggested a possible involvement of APOBEC3A, REV1, UNG, and FHIT in molecular processes affecting APOBEC mutagenesis. It is important to understand how mutagenic processes linked to the activity of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 102 publications
1
8
0
Order By: Relevance
“…The result suggested that APOBECs might act strongly in this region of the minus‐strand in HCC cells. This phenomenon may be attributable to the high expression of APOBECs during the development and progression of HCC cells, so that more APOBECs in cancer cells would be packaged into the viral capsid, which exerts a stronger effect on HBV minus‐strand DNA. In view of the above characteristics of HCC‐derived HBV DNA, it may be possible to identify HCC by APOBEC‐induced mutation pattern of HBV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…The result suggested that APOBECs might act strongly in this region of the minus‐strand in HCC cells. This phenomenon may be attributable to the high expression of APOBECs during the development and progression of HCC cells, so that more APOBECs in cancer cells would be packaged into the viral capsid, which exerts a stronger effect on HBV minus‐strand DNA. In view of the above characteristics of HCC‐derived HBV DNA, it may be possible to identify HCC by APOBEC‐induced mutation pattern of HBV DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Activation-induced cytidine deaminase required class switch recombination and somatic hypermutation; during the process, UNG promotes the former one and suppresses the latter one 1113. Moreover, there was also a negative correlation between UNG expression and APOBEC3B (apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3) in mature B-cell lymphoma cells 13. An important carcinogenic factor is a viral infection which may be caused by up-regulation of APOBEC3B 13.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there was also a negative correlation between UNG expression and APOBEC3B (apolipoprotein B mRNA-editing enzyme, catalytic polypeptide-like 3) in mature B-cell lymphoma cells 13. An important carcinogenic factor is a viral infection which may be caused by up-regulation of APOBEC3B 13. APOBEC3B gene up-regulation increased cancer risk with 5–10% up-regulated in lower end spectrum tumors and nearly 90–95% up-regulated in higher end spectrum tumors 1416.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The A3A is thought to play a role in restricting foreign infectious DNA viruses [ 96 , 97 , 98 , 99 , 100 ] and in restricting internal retroelements [ 101 , 102 , 103 ]. However, elevated expression or/and defective regulation of A3A can also lead to mutations of genomic DNA and contribute to various diseases, including cancer [ 100 , 104 , 105 , 106 ]. More recently, A3A is also shown to deaminate RNA substrates bearing specific structural features [ 107 , 108 ], and editing of RNA by A3A is shown to occur in tumor cells [ 109 ].…”
Section: Apobec3a (A3a)mentioning
confidence: 99%